P239 A novel approach to neuromodulation using transcranial magnetic stimulation-based neurofeedback. Issue 3 (March 2017) - Ruddy, K.; Wenderoth, N.
Abstract : Introduction: Various transcranial brain stimulation techniques have been used in an attempt to modulate excitability of the human corticomotor system, often with weak or mixed results. To date, there exists no reliable method to robustly upregulate or downregulate the output of the motor system. Objectives: Using a novel neurofeedback approach, our goal was to train participants to achieve endogenous neuromodulation by making them consciously aware of the size of their motor evoked potentials (MEPs) in response to transcranial magnetic stimulation (TMS). The goal was to harness experimental control over the excitability of the motor system, in order to investigate the oscillatory brain activity that mediates these states, using electroencephalography (EEG). Materials and methods: Separate sessions were carried out for 'upregulation (UP)' and 'downregulation (DOWN)' of MEP amplitude. In the UP condition subjects were rewarded for larger than average first dorsal interosseous (FDI) MEPs, with visual feedback showing amplitude as a green bar, a positive sound-byte, and a small financial incentive. Smaller than average MEPs were not rewarded, a red bar displayed the amplitude, and a negative sound-byte was heard. The reverse occurred in the DOWN sessions. Background muscle activity was monitored throughout and each trial would not begin until muscles were sufficiently relaxed. The final blocks of training occurred during simultaneous EEG recording. Results: MEP amplitudes in the muscle from which neurofeedback was provided were significantly altered from baseline by the end of 120 training trials ( p = 0.002). Additionally, MEP amplitudes remained altered (UP or DOWN) following training when neurofeedback was removed ( p < 0.001). No changes in MEP amplitude occurred in a nearby control muscle which was not providing neurofeedback. Preliminary EEG data collected during upregulation and downregulation suggests that these two states are mediated by distinct oscillatory signatures. Conclusion: Our approach uses brain stimulation in a non-traditional way to achieve robust endogenous neuromodulation. Using this method to harness experimental control over the excitability of the motor system opens many possibilities for future investigations of how altered brain state influences motor behaviour.